RESEÑA de: Illanes, Inmaculada; Travieso, Mercedes (eds.). El mar: imágenes y escrituras. Berna [etc] : Peter Lang, 2013. - Yllera, Alicia (Signa: Revista de la Asociación Española de Semiótica, 2014)
-